(untitled) (Research, Society and Development, 2022)
This article aims to discuss the phenomenon of social representations, starting from a reflection on related theoretical proposals – narratives and habitus – that contribute to the understanding and application of the theory of social representations, especially under the structural perspective and the theory of the central core. The methodological approach is transdisciplinary between knowledge of Psychology, Sociology, Philosophy and Law, presenting theoretical contributions from all fields to demonstrate the correct perspective of Serge Moscovici and Denise Jodelet regarding the methodological plurality of the phenomenon and the integrated knowledge that permeates it. The article is divided into the following sections: seeking to know the phenomenon between philosophy and social psychology; social representations and their transdisciplinary theorization; and structural approach to legal and social language.